Corn-Cob-Waste-Based Fe2.75Mn0.25O4/rGO Nanocomposite Application as Anti-Radar Coatings - Saefullah, Lalu; Kormil Saputra; Wida Puteri Agista; Masruroh; Dionysius J. D. H. Santjojo; Istiroyah (Science and Technology Indonesia, 2024)
Radar-absorbent materials (RAMs) have become essential technologies in fields that require them, such as the military. Their working principle is that they absorb electromagnetic waves and prevent their reflection. In developing the manufacturing of RAMs, high-performance materials are needed for effective use as RAMs. In general, RAMs possess two essential properties: magnetic and dielectric. This research reports the author’s successful synthesis of an Fe2.75Mn0.25O4/rGO nanocomposite as an anti-radar material using the coprecipitation method. Interestingly, the main precursors used were natural materials, namely iron sand and corn cob waste. XRD, FTIR, and SEM-EDX characterized the research samples to determine the nanocomposite’s structure and phase, functional groups, and morphology after doping. XRD characterization results showed that Fe2.75Mn0.25O4/rGO nanoparticles had a cubic crystal structure and that there were no new peaks, which indicates that Mn had been successfully substituted into Fe. FTIR test results showed that the Fe2.75Mn0.25O4/rGO nanocomposite had Mn and Fe-O functional groups in octahedral and tetrahedral positions at wave numbers of 418 480 cm-1 and that there were C=C functional groups at the wave number of 1629 cm-1. SEM results showed that the nanocomposite comprised Fe2.75Mn0.25O4/rGO particles in agglomerated spheres and corn-cob-based rGO in sheet form, with a grain size of around 26–31 nm. EDX test results showed the appearance of Fe, Mn, O, and C elements. It was also found that the 3-mm-thick Fe2.75Mn0.25O4/rGO nanocomposite sample achieved the highest reflection loss (RL) value of -43.6 dB at a frequency of 8.5 GHz, indicating a significant radar wave absorption capability.